Model Pembinaan Karakter Religius Berbasis Kegiatan Shalat Dhuha Di Madrasah Ibtidaiyah Muhammadiyah 27 Surabaya - Imam Subeki Firmanto; Eli Masnawati (Journal of Research and Community Service, 2025)
Religious character education has become an urgent priority in Islamic schooling amid the growing concern about moral degradation and spiritual detachment among young learners. This study aims to develop a model of religious character development based on the implementation of the Dhuha prayer as a daily spiritual practice at Madrasah Ibtidaiyah Muhammadiyah 27 Surabaya. Employing a qualitative descriptive design with the Asset-Based Community Development (ABCD) approach, this research involved teachers, students, and school leaders as key participants. Data were collected through observations, in-depth interviews, and documentation, then analyzed using Miles and Huberman’s interactive model. The findings reveal that the systematic implementation of the Dhuha prayer before learning activities has significantly strengthened students’ religious awareness, discipline, sense of responsibility, and gratitude. The process of internalizing these values occurs through four integrated stages: spiritual awareness (awareness), value internalization (internalization), habituation (habitualization), and character formation (characterization). This model demonstrates that consistent spiritual routines embedded in the school’s culture can foster a sustainable transformation of students’ behavior and attitudes. Practically, the study provides an applicable model for Islamic schools seeking to cultivate religious character through daily worship-based habituation programs. Theoretically, it contributes to the enrichment of character education discourse by integrating the ABCD framework with Islamic pedagogical principles. Future research is recommended to quantitatively examine the effectiveness of this model in broader educational contexts.